Age‐at‐onset‐dependent effects of sulfur amino acid restriction on markers of growth and stress in male F344 rats. Issue 7 (22nd June 2020) - Nichenametla, Sailendra N.; Mattocks, Dwight A. L.; Malloy, Virginia L
Abstract: Trade‐offs in life‐history traits are clinically and mechanistically important. Sulfur amino acid restriction (SAAR) extends lifespan. But whether this benefit comes at the cost of other traits including stress resistance and growth is unclear. We investigated the effects of SAAR on growth markers (body weight, IGF1, and IGFBP3) and physiological stresses. Male‐F344 rats were fed control (0.86% Met) and SAAR (0.17% Met) diets starting at 2, 10, and 20 months. Rats were injected with keyhole‐limpet‐hemocyanin (KLH) to measure immune responses (anti‐KLH‐IgM, anti‐KLH‐IgG, and delayed‐type‐hypersensitivity [DTH]). Markers of ER stress (FGF21 and adiponectin), detoxification capacity (glutathione [GSH] concentrations, GSH‐S‐transferase [GST], and cytochrome‐P450 ‐reductase [CPR] activities), and low‐grade inflammation (C‐reactive protein [CRP]) were also determined. SAAR decreased body weight, liver weight, food intake, plasma IGF1, and IGFBP3; the effect size diminished with increasing age‐at‐onset. SAAR increased FGF21 and adiponectin, but stress damage markers GRP78 and Xbp1s/us were unchanged, suggesting that ER stress is hormetic. SAAR increased hepatic GST activity despite lower GSH, but CPR activity was unchanged, indicative of enhanced detoxification capacity. Other stress markers were either uncompromised (CRP, anti‐KLH‐IgM, and DTH) or slightly lower (anti‐KLH‐IgG). Increases in stress markers were similar across all ages‐at‐onset, except for adiponectin, which peaked at 2 months. Overall, SAAR did not compromise stress responses and resulted in maximal benefits with young‐onset. In survival studies, median lifespan extension with initiation at 52 weeks was 7 weeks ( p  = .05); less than the 33.5‐week extension observed in our previous study with 7‐week initiation. Findings support SAAR translational studies and the need to optimize Met dose based on age‐at‐onset. Abstract : Trade‐offs between the life‐history traits, growth, stress responses, and lifespan in sulfur amino acid restriction (SAAR). SAAR‐induced lifespan extension trade‐offs with growth but not stress responses. Note : Young, adult, and old represent onset of the intervention in 2‐month‐old, 10‐month‐old, and 20‐month‐old male F344 rats, respectively. SAAR – sulfur amino acid‐restricted diet (0.17% methionine without cysteine), CD – control diet (0.86% methionine without cysteine).